A kind of free-cutting die steel and preparation method thereof

By optimizing the element composition and proportion, using technologies such as solid solution strengthening, alloy carbides and protective oxide layers, the problems of insufficient wear resistance, corrosion resistance, heat resistance and crack resistance during processing of plastic mold steel are solved. , achieving efficient processing and stability improvement of mold steel.

CN118497610BActive Publication Date: 2024-12-20NINGBO JINHAO MOLD MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410622833.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-20
Publication Date
2024-12-20
Estimated Expiration
2044-05-20

AI Technical Summary

Technical Problem

During the processing process, existing plastic mold steels have problems such as insufficient wear resistance, corrosion resistance, heat resistance and crack resistance. The increase in sulfur content leads to a decrease in the surface tension of the steel water, difficulty in separation of steel slag, and resulting in surface defects and cracks of steel.

Method used

Mold steel composed of specific elements, including C, Cr, Co, Ce, Mn, Si, Ni, Cu, Sn and N, is formed by solid solution strengthening, alloy carbide formation, protective oxide layer and copper-nickel enrichment layer, etc. Means to optimize the proportion of elements to improve the cutting performance, wear resistance, corrosion resistance and crack resistance of mold steel.

Benefits of technology

The excellent cutting performance, good wear resistance, corrosion resistance, heat resistance and crack resistance of mold steel are achieved, and the sulfur content is reduced to less than 0.003%. At the same time, the steel material yield is controlled, and the processing accuracy and stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application specifically discloses a free-cutting die steel and a preparation method thereof, wherein the die steel is composed of the following elements in mass percentage: C: 0.18-0.25%, Cr: 1.40-1.60%, Ce≤0.015%, Co: 0.025-0.03%, Mn: 1.16-1.38%, Si: 0.26-0.39%, Ni: 0.1-0.15%, Cu: 0.1-0.2%, S≤0.003%, Sn: 0.02-0.04%, N: 0.05-0.15%; the remainder is iron and unavoidable impurities. The Fe matrix is ​​strengthened and modified by using elements such as Cr, Co, Ce, Mn, Si, Ni, Cu, Sn, and N. Under the joint action of the above elements, the die steel can have excellent cutting performance, good wear resistance, corrosion resistance, heat resistance, and crack resistance at a relatively low addition amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of steel materials, and more specifically, to a free-cutting die steel and a preparation method thereof. Background Art

[0002] Mold steel refers to special steel used to make molds. Mold steel can be divided into plastic mold steel, die-casting mold steel and other types according to its use and working environment. Plastic mold steel generally uses a temperature of 60 to 120°C and is suitable for making molding molds for plastic products such as injection molding and extrusion. Since the hot plastic melt in the production process of plastic products scours and wears the plastic mold steel, and there are raw materials such as polyvinyl chloride and fluorine-containing polymers in the plastic melt, the corrosive components such as hydrogen chloride and hydrogen fluoride produced in the production process are easy to corrode the surface of the plastic mold steel. Therefore, it is necessary to make the mold steel have good wear resistance, corrosion resistance and heat resistance. At the same time, since the cavity structure of plastic molds is generally more complex, in order to improve the final product precision of plastic products, it is necessary to make the mold steel have better easy-to-cut processing performance.

[0003] At present, plastic mold steel mostly uses 4Cr13 series steel, which contains a small amount of sulfur, and the content of sulfur is generally less than or equal to 0.03%. In the related art, in order to improve the cutting performance of plastic mold steel, the general method is to increase the sulfur content so that the sulfur content is less than or equal to 0.05%. After actual attempts, the applicant has adopted methods such as direct addition of sulfur powder, direct addition of industrial-grade ferrous sulfide, and direct addition of pyrite powder to increase the sulfur content. However, it was found in the production process that the difficulty of controlling the sulfur content increased significantly, and the sulfur content was ultimately above 0.05%. As the sulfur content in the steel increases, the surface tension of the molten steel is greatly reduced, making it difficult to separate the slag, resulting in large surface defects on the steel. The steel is prone to cracks during the tempering process, which seriously affects the yield of the mold steel.

[0004] Based on the above situation, how to make plastic mold steel have excellent cutting performance, good wear resistance, corrosion resistance, heat resistance and crack resistance is a problem that needs to be solved urgently in this field. Summary of the invention

[0005] The present application provides a free-cutting die steel and a preparation method thereof, so that the die steel can obtain better processing performance.

[0006] In the first aspect, the present application provides a free-cutting die steel, which adopts the following technical solution:

[0007] A free-cutting die steel composed of the following elements in percentage by mass:

[0008] C: 0.18~0.25%, Cr: 1.40~1.60%, Ce≤0.015%, Co: 0.025~0.03%, Mn: 1.16~1.38%, Si: 0 .26~0.39%, Ni: 0.1~0.15%, Cu: 0.1~0.2%, S≤0.003%, Sn: 0.02~0.04%, N: 0.05~0.15%;

[0009] The balance is iron and unavoidable impurities.

[0010] By adopting the above technical solution, part of the C element enters the steel matrix to cause solid solution strengthening, and the other part can be dispersed in the mold steel to precipitate alloy carbides, thereby ensuring the strength and wear resistance of the plastic mold steel;

[0011] Cr plays a role in solid solution strengthening. On the one hand, it can combine with C to form carbides when the C content is low, so that the low-carbon mold steel maintains a certain hardness and wear resistance, and at the same time, indirectly improves the cutting performance of the mold steel; at the same time, because the corrosion potential of Cr is more negative than that of Fe, it can passivate Fe and improve the corrosion resistance of plastic mold steel; in addition, Cr plays a good selective oxidation role in combination with Ce. Compared with Fe, it is easier to combine with S and O elements, which can avoid the formation of low-melting-point sulfides FeS on the grain boundaries, forming a protective oxide layer, reducing the internal oxidation problem of the matrix caused by the increase in Ni content, thereby significantly improving the heat resistance of the mold steel;

[0012] Co can accelerate the diffusion of solutes, making up for the defect that the large radius of Ce atoms leads to the obstruction of the diffusion of the matrix solid-liquid front, and assist in solid solution strengthening; at the same time, it hinders the segregation caused by the combination of Cr, Mn, Si with S and O, thereby improving the toughness of the mold steel;

[0013] Mn is a solid solution strengthening element in steel, and together with N, Co and other elements, it plays a role in refining grains. In addition, since Cr is easier to combine with S than Mn and other elements, it reduces the formation of rod-shaped sulfides formed by MnS. By combining Cr and Mn elements with a small amount of addition, the mold steel has good toughness and wear resistance, corrosion resistance and heat resistance.

[0014] Si is used to strengthen ferrite. Si can preferentially form oxides in strong oxidizing media. The more positive the pitting potential, the better the chloride ion corrosion resistance. At the same time, since elements such as Cr and Mn are added to the mold steel substrate, they work together with Si to achieve solid solution strengthening and corrosion resistance. Therefore, reducing the amount of Si added can also ensure good corrosion resistance and avoid the problem of carbide particle diameter increasing due to excessive Si addition.

[0015] Ni and Cu work together to form a copper-nickel enriched layer on the steel surface. The copper-nickel enriched layer has good lubrication and thermal conductivity. On the one hand, it can reduce the friction between the slope surface of the tool and the mold steel, thereby improving the cutting performance of the mold steel. At the same time, due to the low melting point of Sn, under the high thermal conductivity of the copper-nickel enriched layer, Sn can soften quickly, effectively play a lubricating role, and the chips are easy to curl. When S is reduced to below 0.003%, it still has good cutting performance.

[0016] N plays a role in refining grains, preventing elements such as Cu and Mn from forming rod-shaped particles. The grain size of the mold steel matrix becomes smaller, and the phase interface area increases, thereby preventing crack propagation. It works together with Co to reduce the average segregation concentration and improve the corrosion resistance and toughness of the mold steel. In addition, N increases the solubility of eutectic carbides in austenite. At higher temperatures, carbides will dissolve in large quantities, and the carbides are small and evenly distributed, so that the hardness of the mold steel is moderate, which is conducive to mechanical processing.

[0017] In summary, the present application adopts elements such as Cr, Co, Ce, Mn, Si, Ni, Cu, Sn, and N to strengthen and modify the Fe matrix. Under the joint action of the above elements, the mold steel can have excellent cutting performance, good wear resistance, corrosion resistance, heat resistance, and cracking resistance at a relatively low addition amount.

[0018] Furthermore, in the free-cutting die steel, the mass percentages of C, Cr, Co and Ce are related as follows: c ×W Cr ×W Co =W Ce , where W C is the mass percentage of C, W Cr is the mass percentage of Cr, W Co is the mass percentage of Co, W Ce is the mass percentage of Ce.

[0019] Furthermore, in the free-cutting die steel, the mass percentage of C is 0.20-0.22%, and the mass percentage of Cr is 1.45-1.50%.

[0020] Furthermore, in the free-cutting die steel, the mass percentages of Cr, Mn and Si are related as follows: Cr / (W Mn +W Si )=0.9~1.0, where W Cr is the mass percentage of Cr, W Mn is the mass percentage of Mn, W Si is the mass percentage of Si.

[0021] Furthermore, in the free-cutting die steel, the mass percentages of Ni, Cu and Sn are related as follows: Sn / (W Ni ×W Cu )=1.5~2.0, where W Ni is the mass percentage of Ni, W Cu is the mass percentage of Cu, W Sn is the mass percentage of Sn.

[0022] Furthermore, in the free-cutting die steel, the mass percentages of Ni, Cu, Sn and S are related as follows: k×W Ni ×W Cu ×W Sn =W S , where W Ni is the mass percentage of Ni, W Cu is the mass percentage of Cu, W Sn is the mass percentage of Sn, W S is the mass percentage of S, and the coefficient of k ranges from 3.5 to 5.

[0023] Furthermore, in the free-cutting die steel, the mass percentage of Ni is 0.12-0.13%, and the mass percentage of Cu is 0.15-0.16%.

[0024] Furthermore, in the free-cutting die steel, the mass percentages of N, Co, Cr, Mn and Cu are related as follows: N +W Co ) / (W Mn +W Cu )=0.06~0.08,W N is the mass percentage of N, W Co is the mass percentage of Co, W Cu is the mass percentage of Cu, W Mn is the mass percentage of Mn.

[0025] By adopting the above technical solution, firstly, the addition amount of each element is adjusted so that the non-metallic inclusions such as carbides and sulfides inside the mold steel substrate are evenly distributed, and the particle size is reduced, thereby reducing the possibility of rod-shaped non-metallic inclusions inside the substrate;

[0026] Secondly, under the joint action of Cu, Ni, S and Sn, the heat generated by cutting can be quickly transferred to the substrate surface during the cutting process of mold steel. The low melting point Sn melts and wets the surface of the mold steel substrate, reducing the cutting friction. The MnS and other particles mixed in the copper-nickel enriched layer form stress concentration points, making it easier to cut.

[0027] Furthermore, since Cr, Ce, and Si can combine with O before Fe and Ni to form a protective oxide layer, the more positive the pitting potential, the better the corrosion resistance to chloride ions, which helps to improve the corrosion resistance of mold steel; at the same time, the content of non-metallic inclusions in the mold steel substrate is small, the thermal conductivity is high, the thermal conductivity is excellent, and the inclusion particles are small and uniform, the mold steel has excellent toughness and can have excellent crack resistance at high temperatures. Therefore, mold steel has excellent cutting performance, good wear resistance, corrosion resistance, heat resistance, and crack resistance.

[0028] In a second aspect, the present application provides a method for preparing free-cutting die steel, which adopts the following technical solution:

[0029] A method for preparing free-cutting die steel comprises the following steps:

[0030] The free-cutting die steel is obtained through primary smelting in electric arc furnace, refining in AOD furnace, refining in LF furnace, annealing, electroslag remelting and hot rolling.

[0031] By adopting the above technical solution, the present application makes innovative adjustments to the composition of steel and combines processes such as electroslag remelting to improve the purity of molten steel, significantly reduce the carbon and sulfur content of mold steel, make the chemical composition uniform, and reduce the possibility of smelting component segregation. This makes the production of mold steel easy to control and enables continuous and stable production. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the technical solutions of the present application are further described below in conjunction with embodiments and comparative examples. Example

[0033] Examples 1-8

[0034] A free-cutting die steel is formulated according to the mass percentages listed in Table 1 below.

[0035]

[0036] Prepare according to the following steps:

[0037] Electric arc furnace refining: The raw materials are high-quality scrap steel, return materials and ferroalloys, which are proportioned according to the mass percentage of each element recorded in Table 1 and fed into the electric arc furnace for steelmaking;

[0038] Refining outside the furnace: smelting with steel in AOD / VOD furnace, oxygen decarburization, reduction refining, temperature measurement and sampling;

[0039] LF refining: Refining temperature rises, after the end of the molten steel leaving the station temperature is 1656℃, and continuous casting annealing is carried out;

[0040] Annealing treatment: the continuous casting temperature is controlled at 1550℃~1580℃, and the 180×180mm square billet is continuously cast at a pulling speed of 0.7~0.75m / min. After the billet is pulled out, the hot transport trolley furnace is kept at 800~850℃ for 3~4h for annealing;

[0041] Electroslag remelting: The billet produced by continuous casting is cut into 3.68-3.70m long and used as electrode billet. The electroslag remelting furnace with constant melting rate and argon protection can accurately control the melting rate to 5.4-7.2kg / min, the stable voltage to 400-600V, and the current to 6000-8000A to ensure the metallurgical quality of electroslag ingot. The smelting ingot shape is 300×300mm square.

[0042] Hot rolling: The electroslag ingot is heated by a pusher furnace at a heating temperature of 1250°C and a holding time of 4 to 6 hours. After the ingot is opened, it is directly hot-transferred to the subsequent continuous rolling unit for continuous rolling to obtain easy-to-cut plastic mold steel. Comparative Example

[0043] Comparative Examples 1-8

[0044] A mold steel, the difference from Example 1 is that the mass percentage of each element is different, as shown in Table 2 below.

[0045]

[0046] The mass percentage composition of each element in the 4Cr13 series steel is as follows: C 0.39%, Si 0.34%, Mn 0.36%, P 0.024%, S 0.003%, Cr 13.25%, V 0.085%, N 0.015%, and the balance is iron and inevitable impurities.

[0047] Performance Testing

[0048] 1. Physical properties

[0049] 1.1 Hardness test: Refer to GB / T230.1 and use a hardness tester to test the hardness of plastic mold steel.

[0050] 1.2 Impact toughness: Refer to the test method recorded in GB / T35840.3-2018 to test the toughness of plastic mold steel, unit J.

[0051] 1.3 Corrosion resistance: Plastic mold steel samples were sent to the salt spray test chamber for salt spray test and taken out after 120 hours. The corrosion resistance of the test steel was evaluated by the degree of pitting corrosion. The degree of pitting corrosion was expressed by the corrosion rate W: W=(W0-W1)×10 6 / (S×t), where W0 is the mass of the plastic mold steel sample before the corrosion test, W1 is the mass of the plastic mold steel sample after corrosion and rust removal, S is the surface area of ​​the plastic mold steel sample, t is the corrosion time, and W is in g / (m 2 h).

[0052] 1.4 Wear amount: record the initial thickness H0 of the plastic mold steel. After the plastic mold steel is used for injection molding 1000 times, clean and remove the plastic residue on the surface of the plastic mold steel, and record the final thickness H1 of the plastic mold steel. The wear amount ΔH = H0- H1.

[0053] 2. Anti-cracking performance

[0054] 2.1 Production crack situation: At room temperature, use ultrasound to detect the edges and cores of plastic mold steel samples and record the number of cracks.

[0055] 2.2 High temperature crack situation: The plastic mold steel was heated to 300°C and then cooled to room temperature. The heating and cooling steps were repeated 10 times. Ultrasonic flaw detection was performed on the edge and core of the plastic mold steel sample, and the number of cracks was recorded.

[0056] 3. Processing performance

[0057] The minimum cutting force that can be processed for the plastic mold steel sample and the wear of the milling cutter after continuously cutting the plastic mold steel sample at a cutting speed of 100 times per minute for 120 hours were recorded. The lower the processable cutting temperature and the less the wear of the milling cutter, the easier the mold steel material is to process and the higher the processing accuracy.

[0058]

[0059] Combining Example 1 and Comparative Examples 1-2 and Table 3, it can be seen that Comparative Example 1 lacks Ce. Although the processing performance is better than that of Example 1, the toughness of Comparative Example 1 is poor and it is easy to crack. The reason may be that the lack of Ce makes it more difficult for Cr to combine with S and O, and a large number of cracks appear in the mold steel matrix. The internal oxidation problem of Ni is significant. It is difficult to overcome the internal oxidation problem of Ni by relying solely on a low content of Si, which causes the mold steel matrix to crack easily in the subsequent forging process, and during use, it is severely corroded by the plastic melt, resulting in poor corrosion resistance and cracking resistance of the mold steel.

[0060] Comparative Example 2 lacks Co, and its hardness and notched impact strength are both lower than those of Example 1. This proves that the lack of Co in the mold steel will hinder the diffusion of elements such as Cr and Mn, thereby causing the particle size of the matrix to be larger, the stress concentration points to increase, and the hardness and toughness to decrease significantly.

[0061] Combining Example 1 with Comparative Examples 3-4 and Table 3, it can be seen that the Ni content in Comparative Example 3 is low, and the Ni content in Comparative Example 4 is high; in Comparative Example 3, due to the low Ni content, part of the copper is difficult to dissolve and diffuse in the mold steel matrix, resulting in an increased possibility of copper cracks and more cracks in the mold steel; and in the later stage of high-temperature cyclic use, due to the low melting point of copper, it is easily corroded by the plastic melt. In Comparative Example 4, the Ni content is too high, which leads to serious internal oxidation of the mold steel matrix, high wear of the mold steel during use, and reduced corrosion resistance.

[0062] Combining Example 1 and Comparative Examples 5-6 with Table 3, it can be seen that the Cu content in Comparative Example 5 is relatively low, and the Cu content in Comparative Example 6 is relatively high; in Comparative Example 5, since part of Ni and copper cannot be well combined, the mold steel has poor thermal cracking resistance and poor corrosion resistance; although Comparative Example 6 has excellent processing performance, Comparative Example 5 has low notch impact strength and high brittleness, and its copper crack possibility is significantly increased.

[0063] Combining Example 1 and Comparative Examples 7-8 with Table 3, it can be seen that the N content in Comparative Example 7 is too low, the grains inside the mold steel are difficult to refine, and the carbides and sulfides of the mold steel are prone to form large-size inclusions, resulting in reduced comprehensive performance. The N content in Comparative Example 8 is too high, although it can improve the toughness of the mold steel, but the N content is too high, stratification is easy to occur inside the mold steel, and cracks between grain boundaries are large, resulting in reduced corrosion resistance and crack resistance.

[0064] Compared with the existing 4Cr13 steel in combination with Example 1, in the present application, elements such as Cr, Co, Ce, Mn, Si, Ni, Cu, Sn and N are innovatively added, and the mass percentage of each element is appropriately adjusted, so that uniform and fine inclusions are formed inside the mold steel, thereby increasing the hardness, toughness and corrosion resistance of the mold while improving its crack resistance and processing performance.

[0065] In contrast to Examples 1-2 and 3-4, the relationship among C, Cr, Co, Ce, Mn, Si, Ni, Cu, Sn and N in Examples 3-4 satisfies the following relationship: c ×W Cr ×W Co =W Ce , W Cr / (W Mn +W Si )=0.9~1.0,W Sn / (W Ni ×W Cu )=1.5~2.0, k×W Ni ×W Cu ×W Sn =W S(k coefficient range is 3.5~5) and (W N +W Co ) / (W Mn +W Cu )=0.06~0.08. According to the test data of Examples 1-2 and 3-4, it can be seen that the addition amount of each element in Example 3-4 satisfies the above relationship, while Example 1-2 does not satisfy the above relationship. Although the mass percentages of C and Cr are the same, the physical property test value of Example 1 is lower than that of Example 3, and the test values ​​of anti-cracking performance and processing performance are higher than those of Example 3. The physical property test value of Example 2 is lower than that of Example 4, and the test values ​​of anti-cracking performance and processing performance are higher than those of Example 4. It can be seen that the mold steel can significantly improve its comprehensive performance if it satisfies the above relationship.

[0066] In contrast to Example 3-4 and Example 5-8, the difference between Example 3-4 and Example 5-8 is that the Cr and C contents of Example 5-8 are within the preferred range values, and the comprehensive performance of the mold steel can be significantly improved through further optimization of each element.

[0067] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0068] Moreover, the above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A free-cutting die steel, characterized in that: The following elements are present in mass percentage composition: C: 0.18~0.25%, Cr: 1.40~1.60%, Ce≤0.015%, Co: 0.025~0.03%, Mn: 1.16~1.38%, Si: 0 .26~0.39%, Ni: 0.1~0.15%, Cu: 0.1~0.2%, S≤0.003%, Sn: 0.02~0.04%, N: 0.05~0.15%; The balance is iron and unavoidable impurities; Among them, the mass percentages of C, Cr, Co and Ce have the following relationship: c ×W Cr ×W Co =W Ce , where W C is the mass percentage of C, W Cr is the mass percentage of Cr, W Co is the mass percentage of Co, W Ce is the mass percentage of Ce.

2. The free-cutting die steel according to claim 1, characterized in that: In the free-cutting die steel, the mass percentage of C is 0.20-0.22%, and the mass percentage of Cr is 1.45-1.50%.

3. The free-cutting die steel according to claim 1, characterized in that: In the free-cutting die steel, the mass percentages of Cr, Mn and Si are related as follows: Cr / (W Mn +W Si )=0.9~1.0, where W Cr is the mass percentage of Cr, W Mn is the mass percentage of Mn, W Si is the mass percentage of Si.

4. The free-cutting die steel according to claim 1, characterized in that: In the free-cutting die steel, the mass percentages of Ni, Cu and Sn are related as follows: Sn / (W Ni ×W Cu )=1.5~2.0, where W Ni is the mass percentage of Ni, W Cu is the mass percentage of Cu, W Sn is the mass percentage of Sn.

5. The free-cutting die steel according to claim 4, characterized in that: In the free-cutting die steel, the mass percentages of Ni, Cu, Sn and S are related as follows: k×W Ni ×W Cu ×W Sn =W S , where W Ni is the mass percentage of Ni, W Cu is the mass percentage of Cu, W Sn is the mass percentage of Sn, W S is the mass percentage of S, and the coefficient of k ranges from 3.5 to 5.

6. The free-cutting die steel according to claim 5, characterized in that: In the free-cutting die steel, the mass percentage of Ni is 0.12-0.13%, and the mass percentage of Cu is 0.15-0.16%.

7. The free-cutting die steel according to claim 1, characterized in that: In the free-cutting die steel, the mass percentages of N, Co, Mn and Cu are related as follows: N +W Co ) / (W Mn +W Cu )=0.06~0.08,W N is the mass percentage of N, W Co is the mass percentage of Co, W Cu is the mass percentage of Cu, W Mn is the mass percentage of Mn.

8. The method for preparing free-cutting die steel according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: primary smelting in an electric arc furnace, refining in an AOD furnace, refining in an LF furnace, annealing treatment, electroslag remelting and hot rolling to obtain easy-to-cut die steel.